Trace metals in surface sediments from the Laptev and East Siberian Seas: Levels, enrichment, contamination assessment, and sources. (December 2021) - Sattarova, Valentina; Aksentov, Kirill; Astakhov, Anatolii; Shi, Xuefa; Hu, Limin; Alatortsev, Alexandr; Mariash, Anna; Yaroshchuk, Elena
Abstract: Trace metals in Laptev and East Siberian Sea sediments were analyzed to examine the element distribution pattern and to assess sediment contamination using contamination indices. The maximum Cr, Zn, Ni, Cu, and As concentrations occurred in the deeper parts of the East Siberian and Laptev Seas and the estuarine shelves of the Lena and Yana Rivers, and a high Cd content was observed in the sediment of the eastern part of the East Siberian Sea. The increased Cd concentration could be a result of the large number of phytoplankton supplied by the highly productive waters of the Bering Sea and the sorption capacity of Cd precipitation on Fe and Mn oxyhydroxides in seawater. The mean enrichment factors and geoaccumulation index values for Cr, Ni, Cu, Zn, Pb, and Cd showed no contamination by these metals at any sampling locations; however, slight As enrichment was found, possibly originating from natural sources. Highlights: Trace metals in sediments from the East Siberian and Laptev Seas were investigated. All trace metals showed a low ecological risk index. Trace metal enrichment is attributed to natural factors.